Caicó: uma cidade entre a recusa e a sedução - Andrade, Juciene Batista Félix (2007)
This research has as object of study the city of Caicó, Rio Grande do Norte State, between the middle part of the decade of 1920 and the beginning of 1930. It intended to perceive the projects thought to the city of Caicó as well as the challenges due to the new ideas of modernity that were circulating around the contemporary world. So it consists in an important historical exercise about the relation between history and space in to the extent that itself comes to surface a city deals by diverse angles whose perspectives can be read in several "fragments of memory", such as newspapers, trials-crime, reports, memories, books, etc., those show the tension between the traditional and the modern way of life one. In this way, it´s tried to transform the space, giving it a new reference, inspired in what occurs in the Brazilian big cities and around the world, through the use of the techniques, of the electricity, of the movies, of the press, cars, medicine and so on. At the same time in that is necessary-itself deal with the permanencies such as the old manners and the droughts and theirs "flagellated" people. Therefore, it is in this difficult phase that is tried legitimize the city of Caicó as the "Capital of the Seridó", in the threshold between the refusal and the seduction